Modified nano barium titanate with strong piezoelectric effect as well as preparation method and application of modified nano barium titanate

By etching the Ba2+ vacancy in barium titanate and filling doped metal ions, modified nanobarium titanate with strong piezoelectric effect was prepared, which solved the problem of low piezoelectric performance of existing piezoelectric materials, and achieved significant improvement in piezoelectric performance and excellent performance in many fields.

CN119768030AActive Publication Date: 2025-04-04CHONGQING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411947041.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The piezoelectric properties of existing piezoelectric materials are relatively low and it is difficult to meet the needs of efficient application in the fields of sewage treatment, full water decomposition, organic synthesis and CO2 reduction.

Method used

Modified nanobarium titanate with strong piezoelectric effect was prepared by etching barium titanate into its crystal lattice and filling the Ba2+ vacancy with doped metal ions by hydrothermal method.

Benefits of technology

The piezoelectric performance of barium titanate was significantly enhanced, and the piezoelectric coefficient increased from 29.2pm/V to 129.9pm/V, an increase of 345%, and showed excellent results in the fields of pollutant degradation and tumor treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768030A_ABST
    Figure CN119768030A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of piezoelectric materials, and discloses modified nano barium titanate with a strong piezoelectric effect and a preparation method and application thereof. The modified nano barium titanate with the strong piezoelectric effect is prepared by etching barium titanate to form Ba < 2 + > vacancies in crystal lattices of the barium titanate and then filling the Ba < 2 + > vacancies with doped metal ions through a hydrothermal method. The doped metal is metal which forms thermal stable ions or coordination ions under an alkaline condition. According to the invention, barium titanate is subjected to etching and secondary hydro-thermal treatment, A-site ion exchange is carried out in surface crystal lattices of barium titanate, radial chemical component gradient and strain gradient are constructed, and a flexoelectric effect is formed; the flexoelectric effect and the piezoelectric effect are coupled, and the piezoelectric performance of barium titanate is enhanced. Compared with the prior art, the piezoelectric coefficient of the treated barium titanate is obviously enhanced to 129.9 pm / V from 29.2 pm / V and is improved by 345%, the piezoelectric property is greatly enhanced, and the barium titanate has excellent performance in the application fields of pollutant degradation, tumor treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of piezoelectric materials, and in particular to a modified nano-barium titanate with a strong piezoelectric effect, and a preparation method and application thereof. Background Art

[0002] The piezoelectric effect is a mechanical-electromagnetic coupling phenomenon in which the internal structure of a non-centrosymmetric crystal shifts under the action of mechanical force, causing the centers of positive and negative charges to separate and generate a built-in electric field, ultimately leading to the accumulation of positive and negative charges on opposite surfaces.

[0003] Materials with piezoelectric effect are called piezoelectric materials. Currently, piezoelectric materials have been widely used in sewage treatment, water decomposition, organic synthesis and CO2 reduction. Among many piezoelectric materials, BaTiO3 has a high piezoelectric coefficient (d 33 ) and good biosafety. BaTiO3 belongs to the typical perovskite structure (ABO3), O 2- Forming a regular octahedron, Ti 4+ Located at the center of the octahedron, Ba 2+ is located in the gap of the octahedron, and its piezoelectricity comes from the Ti 4+ The eccentric displacement induces electron / ion polarization, accompanied by a decrease in the unit cell symmetry from cubic to tetragonal.

[0004] Piezoelectric materials can also be used as sonosensitizers. Thanks to their unique piezoelectric effect, under the action of external ultrasound, piezoelectric sonosensitizers can establish a built-in electric field, while causing the bending of the band structure and inhibiting carrier recombination, greatly enhancing the generation efficiency of ROS. In recent years, a large number of work reports have adopted different strategies to improve BaTiO3-based materials to develop piezoelectric sonosensitizers with better performance, such as ion doping, oxygen vacancy engineering, phase engineering, and heterojunction engineering to improve BaTiO3 carrier lifetime or substrate selectivity.

[0005] However, there are few reports on the improvement of the piezoelectric properties of BaTiO3, and its piezoelectric properties still need to be improved. It is a feasible idea to improve the piezoelectric properties of BaTiO3 by modulating the mechanical force-electromagnetic coupling. The coupling effect between flexoelectricity and piezoelectricity is one of the recently debated ways to manipulate the piezoelectric response, which proposes a direct strategy to enhance the mechanical force-electromagnetic coupling performance. However, since the internal strain gradient of nanoparticles is difficult to control and observe, it is very challenging to control the coupling between flexoelectricity and piezoelectricity. Summary of the invention

[0006] The present application provides a modified nano-barium titanate with a strong piezoelectric effect and a preparation method and application thereof, aiming to solve the problem of low piezoelectric performance of existing piezoelectric materials.

[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0008] In the first aspect of the present application, a modified nano-barium titanate having a strong piezoelectric effect is provided, which is formed by etching barium titanate in its lattice. 2+ Vacancies are then filled with doped metal ions by hydrothermal method. 2+ Prepared by vacancy;

[0009] The doping metal is a metal that forms thermally stable ions or complex ions under alkaline conditions.

[0010] Preferably, the doped metal is at least one of copper, silver, gold or palladium.

[0011] The second aspect of the present application provides a method for preparing the modified nano-barium titanate having a strong piezoelectric effect, comprising:

[0012] S1, dispersing barium titanate in an acid solution, stirring the reaction; collecting the solid phase, washing and drying, obtaining a Ba 2+ Vacant barium titanate;

[0013] S2, the Ba 2+ The vacant barium titanate is dispersed in a doped metal salt solution, and ammonia water is added and mixed to obtain a dispersion;

[0014] The dispersion is transferred to a high-pressure reactor for hydrothermal reaction, and the solid phase is collected, washed and dried to obtain modified nano-barium titanate with a strong piezoelectric effect.

[0015] Preferably, the acid solution is hydrochloric acid with a pH of 3 to 5; and the concentration of the barium titanate in the acid solution is 0.005 to 0.5 mol / L.

[0016] Preferably, the doping metal salt is a water-soluble salt of copper, silver, gold or palladium.

[0017] Further preferably, the doping metal salt is copper chloride or copper nitrate.

[0018] Further preferably, the concentration of the doped metal salt solution is 0.001 to 0.1 mol / L;

[0019] The dispersion has Ba 2+ The concentration of the vacant barium titanate is 0.01-1 mol / L; the concentration of the ammonia water is 1-10 mol / L.

[0020] Preferably, the temperature of the hydrothermal reaction is 120-220° C., and the reaction time is 6-24 hours.

[0021] The third aspect of the present application provides the use of the modified nano-barium titanate with strong piezoelectric effect in piezoelectric catalytic degradation of organic matter.

[0022] The fourth aspect of the present application provides the use of the modified nano-barium titanate with strong piezoelectric effect in tumor treatment drugs.

[0023] Compared with the prior art, the beneficial effects of this application are:

[0024] This application transforms the surface lattice of barium titanate to significantly enhance its piezoelectric properties while preserving the semiconductor properties of the material to the maximum extent. Specifically, this application etches and performs secondary hydrothermal treatment on barium titanate, performs A-site ion exchange in its surface lattice, and constructs radial chemical composition gradients and strain gradients. The strain gradient can break its local inversion symmetry, produce an electric polarization with a specific direction, and achieve a piezoelectric-like response, namely the flexoelectric effect. This application couples the flexoelectric effect with the piezoelectric effect to enhance the piezoelectric properties of barium titanate. After this treatment, the piezoelectric coefficient of barium titanate in this application is significantly enhanced from 29.2pm / V to 129.9pm / V, an increase of 345%.

[0025] The modified nano-barium titanate with strong piezoelectric effect prepared in this application has achieved a great enhancement in piezoelectric performance, far exceeding the improvement of existing technologies, and has excellent performance in the fields of pollutant degradation and tumor treatment. It is used for piezoelectric catalytic degradation of organic matter. After 10 minutes of ultrasonic irradiation, the degradation efficiency of methylene blue (MB) is 1.93 times that of barium titanate; it is used as a tumor treatment drug for tumor-bearing mice, and the tumor inhibition rate reaches 83.7%, while the tumor inhibition rate of barium titanate is only 24.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 SEM, TEM and EDS spectra of BTO prepared for this application;

[0028] Figure 2 SEM, TEM and EDS spectra of Cu-BTO prepared for this application;

[0029] Figure 3 The SEM and EDS spectra of Cu-BTO prepared in comparative example;

[0030] Figure 4 The piezoelectric coefficient test result diagram of Cu-BTO prepared in the examples and comparative examples of the present application;

[0031] Figure 5 This is a diagram showing the piezoelectric catalytic degradation of methylene blue by Cu-BTO prepared in this application;

[0032] Figure 6 This is a diagram showing the therapeutic effect of Cu-BTO prepared in this application on tumors. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0035] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0036] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0038] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0039] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0040] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] In the first aspect, the present application provides a modified nano-barium titanate with a strong piezoelectric effect, which is formed by etching barium titanate in its lattice. 2+ Vacancies are then filled with doped metal ions by hydrothermal method. 2+ Prepared by vacancy;

[0042] The doping metal is a metal that forms thermally stable ions or complex ions under alkaline conditions; in the present application, the doping metal can be selected from at least one of copper, silver, gold or palladium.

[0043] This application can significantly enhance the piezoelectric performance of barium titanate while preserving the semiconductor properties of the material to the maximum extent by modifying the surface lattice of barium titanate. Specifically, this application etches and performs secondary hydrothermal treatment on barium titanate, performs A-site ion exchange in its surface lattice, and constructs radial chemical composition gradients and strain gradients. The strain gradient can break its local inversion symmetry, produce electric polarization with a specific direction, and achieve a piezoelectric-like response, namely the flexoelectric effect. This application couples the flexoelectric effect with the piezoelectric effect to enhance the piezoelectric performance of barium titanate.

[0044] After the treatment, the piezoelectric coefficient of barium titanate in the present application is significantly enhanced from 29.2 pm / V to 129.9 pm / V, an increase of 345%.

[0045] In a second aspect, the present application provides a method for preparing the modified nano-barium titanate having a strong piezoelectric effect, comprising:

[0046] S1, dispersing barium titanate BTO in acid solution, stirring the reaction; collecting the solid phase, washing and drying, obtaining a Ba 2+ Vacant barium titanate, denoted as B 1-x TO;

[0047] In the present application, the acid solution may be hydrochloric acid or nitric acid with a pH of 3 to 5, preferably hydrochloric acid with a pH of 3 to 5; the concentration of the barium titanate in the acid solution is 0.005 to 0.5 mol / L, preferably 0.05 to 0.06 mol / L.

[0048] S2, the Ba 2+ The vacant barium titanate is dispersed in a doped metal salt solution, and ammonia water is added and mixed to obtain a dispersion;

[0049] The dispersion is transferred to a high-pressure reactor for hydrothermal reaction, and the solid phase is collected, washed and dried to obtain modified nano-barium titanate with strong piezoelectric effect, which is recorded as Cu-BTO. The temperature of the hydrothermal reaction is 120-220°C, the reaction time is 6-24 hours, and the preferred reaction time is 18 hours.

[0050] In the present application, the doping metal salt is a water-soluble salt of copper, silver, gold or palladium, preferably a water-soluble salt of copper, such as copper chloride or copper nitrate and hydrates thereof. Preferably, the concentration of the doping metal salt solution is 0.001 to 0.1 mol / L, more preferably 0.008 to 0.024 mol / L.

[0051] In the present application, ammonia water is used to stabilize the doped metal ions to avoid the generation of metal-doped oxides that would damage the final piezoelectric properties of barium titanate.

[0052] Specifically, the present invention stabilizes copper ions by adding ammonia water to avoid the formation of copper oxide impurities, thereby significantly improving the piezoelectric properties of the final modified nano-barium titanate. 1-x TO does not react with copper salts, so it is impossible to fill Ba with copper ions. 2+ Empty position, the final result is still B 1-x TO. If other alkaline solutions are used instead of ammonia water, such as sodium hydroxide solution, copper ions cannot stably exist under high temperature and high pressure alkaline conditions. Under an electron microscope, a large number of flaky copper oxide impurities can be observed, and the purpose of enhancing piezoelectric performance cannot be achieved.

[0053] In the present application, the dispersion has Ba 2+ The concentration of vacant barium titanate is 0.01 to 1 mol / L, preferably 0.3 to 0.4 mol / L, and the concentration of ammonia water is 1 to 10 mol / L, preferably 3 to 5 mol / L. Under these conditions, the effect of enhancing piezoelectric performance is the best.

[0054] The modified nano-barium titanate with strong piezoelectric effect prepared in this application achieves a great enhancement in piezoelectric performance, far exceeding the improvement of existing technologies, and has excellent performance in application scenarios such as pollutant degradation and tumor treatment.

[0055] The modified nano-barium titanate with strong piezoelectric effect prepared in the present application can improve the generation efficiency of active oxygen and can be used for piezoelectric catalytic degradation of organic matter. After 10 minutes of ultrasonic irradiation, its degradation efficiency for methylene blue (MB) is 1.93 times that of barium titanate.

[0056] The modified nano-barium titanate with strong piezoelectric effect prepared in this application contains multiple reactive sites, which can expand substrate selectivity, effectively regulate the tumor inhibition microenvironment, and improve the effect of tumor treatment. It can be used for tumor treatment drugs, or for the preparation of tumor treatment drugs. When it is used as a tumor treatment drug for tumor-bearing mice, the tumor inhibition rate reaches 83.7%, while the tumor inhibition rate of barium titanate is only 24.5%.

[0057] The present application is further described below by way of examples.

[0058] Example 1

[0059] This embodiment provides a method for preparing modified nano-barium titanate with strong piezoelectric effect, comprising:

[0060] Step 1. Preparation of tetragonal barium titanate by hydrothermal method:

[0061] Dissolve 17.02g of tetrabutyl titanate in 20mL of ethanol, stir at 500rpm and add 7mL of ammonia water dropwise to form a uniform white emulsion. Dissolve 14.2g of barium hydroxide in water, inject the above white emulsion at 80°C, stir at 500rpm for 30min, and transfer to a 100mL high-pressure reactor with a polytetrafluoroethylene liner. Place the reactor at 200°C for 48h, wash the white particles obtained by the reaction repeatedly with 5% acetic acid solution and ethanol for 3 times, and dry at 80°C overnight to obtain tetragonal titanic acid, recorded as BTO.

[0062] Step 2. Acid etching of barium titanate to produce Ba 2+ Seats available:

[0063] BTO was evenly dispersed in hydrochloric acid with a pH of 3 to prepare a solution with a BTO concentration of 0.05 mol / L. The solution was stirred at a speed of 500 rpm for 12 hours, and the solid phase was collected. The white particles obtained after etching were washed alternately with water and ethanol for a total of 3 times, and dried at 80°C overnight to obtain Ba 2+ Vacant barium titanate, denoted as B 1-x TO.

[0064] Step 3. Utilize Cu 2+ Filling 2+ Seats available:

[0065] Use copper nitrate trihydrate to prepare a 0.008 mol / L copper salt aqueous solution. 1-x TO is dispersed in a copper salt aqueous solution, where B 1-x The TO concentration is 0.3 mol / L. Ammonia water is then added to the copper salt aqueous solution to make the concentration of ammonia water 3 mol / L to form a purple dispersion. After stirring the dispersion for 30 minutes, it is transferred to a 50 mL high-pressure reactor with a polytetrafluoroethylene liner, and the reactor is placed at 200°C for 18 hours. The solid phase is separated and collected, and the obtained light blue particles are washed with ethanol 3 times and dried at 80°C overnight to obtain modified nano-barium titanate with a strong piezoelectric effect.

[0066] Example 2

[0067] This embodiment provides a method for preparing modified nano-barium titanate with strong piezoelectric effect, comprising:

[0068] Step 1. Preparation of tetragonal barium titanate by hydrothermal method:

[0069] Dissolve 17.02g of tetrabutyl titanate in 20mL of ethanol, stir at 500rpm and add 7mL of ammonia water dropwise to form a uniform white emulsion. Dissolve 14.2g of barium hydroxide in water, inject the above white emulsion at 80°C, stir at 500rpm for 30min, and transfer to a 100mL high-pressure reactor with a polytetrafluoroethylene liner. Place the reactor at 200°C for 48h, wash the white particles obtained by the reaction repeatedly with 5% acetic acid solution and ethanol for 3 times, and dry at 80°C overnight to obtain tetragonal titanic acid, recorded as BTO.

[0070] Step 2. Acid etching of barium titanate to produce Ba 2+ Seats available:

[0071] BTO was evenly dispersed in hydrochloric acid with a pH of 3 to prepare a solution with a BTO concentration of 0.05 mol / L. The solution was stirred at a speed of 500 rpm for 12 hours, and the solid phase was collected. The white particles obtained after etching were washed alternately with water and ethanol for a total of 3 times, and dried at 80°C overnight to obtain Ba 2+ Vacant barium titanate, denoted as B 1-x TO.

[0072] Step 3. Utilize Cu 2+ Filling 2+ Seats available:

[0073] Use copper nitrate trihydrate to prepare a 0.0016 mol / L copper salt aqueous solution. 1-x TO is dispersed in a copper salt aqueous solution, where B 1-x The TO concentration is 0.34 mol / L. Ammonia water is then added to the copper salt aqueous solution to make the concentration of ammonia water 3 mol / L to form a purple dispersion. After stirring the dispersion for 30 minutes, it is transferred to a 50 mL high-pressure reactor with a polytetrafluoroethylene liner, and the reactor is placed at 200°C for 18 hours. The solid phase is separated and collected, and the obtained light blue particles are washed with ethanol three times and dried at 80°C overnight to obtain modified nano-barium titanate with a strong piezoelectric effect.

[0074] Example 3

[0075] This embodiment provides a method for preparing modified nano-barium titanate with strong piezoelectric effect, comprising:

[0076] Step 1. Preparation of tetragonal barium titanate by hydrothermal method:

[0077] Dissolve 17.02g of tetrabutyl titanate in 20mL of ethanol, stir at 500rpm and add 7mL of ammonia water dropwise to form a uniform white emulsion. Dissolve 14.2g of barium hydroxide in water, inject the above white emulsion at 80°C, stir at 500rpm for 30min, and transfer to a 100mL high-pressure reactor with a polytetrafluoroethylene liner. Place the reactor at 200°C for 48h, wash the white particles obtained by the reaction repeatedly with 5% acetic acid solution and ethanol for 3 times, and dry at 80°C overnight to obtain tetragonal titanic acid, recorded as BTO.

[0078] Step 2. Acid etching of barium titanate to produce Ba 2+ Seats available:

[0079] The BTO was evenly dispersed in hydrochloric acid with a pH of 3 to prepare a solution with a BTO concentration of 0.06 mol / L, which was stirred at a speed of 500 rpm for 12 hours, and the solid phase was collected; the white particles obtained after etching were washed alternately with water and ethanol for a total of 3 times, and dried at 80°C overnight to obtain Ba 2+ Vacant barium titanate, denoted as B 1-x TO.

[0080] Step 3. Utilize Cu 2+ Filling 2+ Seats available:

[0081] Use copper nitrate trihydrate to prepare a 0.0024 mol / L copper salt aqueous solution. 1-x TO is dispersed in a copper salt aqueous solution, where B 1-x The TO concentration is 0.4 mol / L. Ammonia water is then added to the copper salt aqueous solution to make the concentration of ammonia water 5 mol / L to form a purple dispersion. After stirring the dispersion for 30 minutes, it is transferred to a 50 mL high-pressure reactor with a polytetrafluoroethylene liner, and the reactor is placed at 200°C for 18 hours. The solid phase is separated and collected, and the obtained light blue particles are washed with ethanol three times and dried at 80°C overnight to obtain modified nano-barium titanate with a strong piezoelectric effect.

[0082] Example 4

[0083] The difference between Example 4 and Example 1 is that in step 3, the reaction kettle is placed at 200° C. for reaction for 12 hours, and the rest is the same as Example 1.

[0084] Example 5

[0085] The difference between Example 5 and Example 1 is that in step 3, the reaction kettle is placed at 200° C. for reaction for 24 hours, and the rest is the same as Example 1.

[0086] Comparative Example

[0087] The difference between the comparative example and Example 1 is that in step 3, sodium hydroxide solution is used instead of ammonia water, and the rest is the same as Example 1.

[0088] The BTO and Cu-BTO prepared in Example 1 and the modified nano-barium titanate prepared in the comparative example were subjected to SEM, TEM and EDS tests. The morphological characteristics of the nanoparticles were directly observed by SEM and TEM, and the elemental composition of the nanoparticles was determined by EDS of TEM.

[0089] The test results are as follows Figure 1 , Figure 2 and Figure 3 As shown. Among them, Figure 1 From left to right are the SEM, TEM and EDS spectra of BTO. Figure 2 From left to right are the SEM, TEM and EDS spectra of Cu-BTO. Figure 3 From left to right are the SEM and EDS spectra of nano-barium titanate prepared in the comparative example.

[0090] from Figure 1-Figure 3 It can be seen that the morphology of BTO and Cu-BTO has not changed significantly, because ammonia stabilizes copper ions and no copper oxide impurities are generated. The EDS element distribution shows that the Cu element is enriched in Cu-BTO, confirming that Cu 2+ Successfully entered the Ba produced by etching 2+ On the contrary, when sodium hydroxide was used instead of ammonia water in the comparative example, a large amount of flaky copper oxide impurities appeared in the nano-barium titanate, which not only failed to enhance the piezoelectric performance, but also may damage its piezoelectric performance.

[0091] The piezoelectric coefficient d of the BTO and Cu-BTO prepared in Example 1 and the Cu-BTO prepared in Examples 4 and 5 was measured by piezoelectric force microscopy (PFM). 33 The value is as follows Figure 4 As shown. Figure 4 It can be seen that the piezoelectric coefficient of Cu-BTO is higher than that of BTO, and the degree of improvement is related to the time of hydrothermal reaction. After the hydrothermal reaction time is 12h, the piezoelectric coefficient of Cu-BTO d 33 increased to 31.98pm / V; and after 18 hours of hydrothermal reaction, the piezoelectric coefficient of Cu-BTO 33 The value rises to 129.91pm / V, which is 345% higher than that of BTO at 29.22pm / V. The enhancement effect is very significant. As the hydrothermal reaction time increases, when the reaction time reaches 24h, the piezoelectric coefficient d 33 The enhancement effect decreases as the hydrothermal reaction proceeds. 2+Gradually enter the Ba produced by etching 2+ After the hydrothermal reaction reaches 12h, Cu 2+ Enter the Ba produced by etching 2+ The number of vacancies began to increase. When the reaction time was 18 h, Cu 2+ Filling 2+ The number of vacancies reaches a maximum; as time goes by, Cu 2+ Filling 2+ The number of vacancies decreases.

[0092] The piezoelectric catalytic degradation effect of BTO and Cu-BTO prepared in Example 1 on methylene blue MB was tested. The specific test method is: BTO and Cu-BTO were dispersed in a 10 mg / L MB solution at a concentration of 1 mg / mL, and the dispersion system was irradiated with ultrasound to start the reaction. 1 mL was taken from the reaction system every 2 minutes, and the supernatant was centrifuged and the absorbance value at 664 nm was detected. The test results are as follows: Figure 5 shown.

[0093] from Figure 5 It can be seen that both BTO and Cu-BTO can cause MB degradation under ultrasound, and the degree of degradation increases with the extension of ultrasound irradiation time. When irradiated for the same time, the degradation intensity of Cu-BTO as piezoelectric catalyst is significantly stronger than that of BTO group, indicating that Cu-BTO has a stronger piezoelectric catalytic effect under ultrasound due to its enhanced piezoelectric properties.

[0094] The therapeutic effects of BTO and Cu-BTO prepared in Example 1 on tumors were tested, and the specific testing method was as follows:

[0095] First, a subcutaneous 4T1 tumor model was established in the right groin of 6-week-old female BALB / c mice. 3 Treatment was started after that. PBS, BTO and Cu-BTO were injected through the tail vein on days 0, 2 and 4 of treatment, respectively. Ultrasound was used to irradiate the tumor site 4 hours after injection. The tumor growth of mice in each treatment group was recorded every other day. The test results are shown in Figure 6 Among them, the PBS+US group received PBS injection through the tail vein and ultrasonic treatment; the BTO+US group received BTO injection through the tail vein and ultrasonic treatment; the Cu-BTO+US group received Cu-BTO injection through the tail vein and ultrasonic treatment.

[0096] from Figure 6It can be seen that the tumor treatment effect of the BTO+US group is only slightly better than that of the PBS+US group, while the treatment effect of the Cu-BTO+US group is significantly better than that of the PBS+US group and the BTO+US group. The tumor inhibition rate of the Cu-BTO+US group reached 83.7%, while the tumor inhibition rate of the BTO+US group was only 24.5%. The test results show that the Cu-BTO prepared in this application can expand substrate selectivity, effectively regulate the tumor inhibition microenvironment, and improve the effect of tumor treatment.

[0097] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A modified nano-barium titanate with strong piezoelectric effect, characterized in that: It forms Ba in its lattice by etching barium titanate 2+ Vacancies are then filled with doped metal ions by hydrothermal method. 2+ Prepared by vacancy; The doping metal is a metal that forms thermally stable ions or complex ions under alkaline conditions.

2. The modified nano barium titanate with strong piezoelectric effect according to claim 1, characterized in that: The doping metal is at least one of copper, silver, gold or palladium.

3. The method for preparing modified nano-barium titanate with strong piezoelectric effect according to claim 1, characterized in that: include: S1, dispersing barium titanate in an acid solution and stirring for reaction; The solid phase was collected, washed and dried to obtain 2+ Vacant barium titanate; S2, the Ba 2+ The vacant barium titanate is dispersed in a doped metal salt solution, and ammonia water is added and mixed to obtain a dispersion; The dispersion is transferred to a high-pressure reactor for hydrothermal reaction, and the solid phase is collected, washed and dried to obtain modified nano-barium titanate with a strong piezoelectric effect.

4. The preparation method according to claim 3, characterized in that: The acid solution is hydrochloric acid with a pH of 3 to 5; The concentration of the barium titanate in the acid solution is 0.005-0.5 mol / L.

5. The preparation method according to claim 3, characterized in that: The doping metal salt is a water-soluble salt of copper, silver, gold or palladium.

6. The preparation method according to claim 5, characterized in that: The doping metal salt is copper chloride or copper nitrate.

7. The preparation method according to claim 6, characterized in that: The concentration of the doped metal salt solution is 0.001 to 0.1 mol / L; The dispersion has Ba 2+ The concentration of the vacant barium titanate is 0.01-1 mol / L; the concentration of the ammonia water is 1-10 mol / L.

8. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 120-220° C., and the reaction time is 6-24 hours.

9. Use of the modified nano-barium titanate with strong piezoelectric effect as claimed in claim 1 or 2 in piezoelectric catalytic degradation of organic matter.

10. Use of the modified nano-barium titanate with strong piezoelectric effect as claimed in claim 1 or 2 in tumor treatment drugs.

Citation Information

Patent Citations

  • Method for preparing barium titanate compounds

    CN103693680A

  • Piezoelectric nano composite material and preparation method thereof

    CN110797453A

  • Preparation method and application of silver / barium titanate photocatalyst

    CN117123217A

  • Piezoelectric effect enhanced sound-sensitive agent as well as preparation method and application thereof

    CN118806895A

  • Method for making metal titanate

    US20080241042A1